2021
DOI: 10.1145/3459009
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Silicon Photonics for Deep Learning

Abstract: Deep learning has led to unprecedented successes in solving some very difficult problems in domains such as computer vision, natural language processing, and general pattern recognition. These achievements are the culmination of decades-long research into better training techniques and deeper neural network models, as well as improvements in hardware platforms that are used to train and execute the deep neural network models. Many application-specific integrated circuit (ASIC) hardware accelerators for deep le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 173 publications
0
19
0
Order By: Relevance
“…While several high-performance AI accelerators based on coherent SP-NNs have been recently proposed [2,10,13], [14] showed that the inferencing accuracy of SP-NNs can drop by up to 70% due to fabrication-process variations and thermal crosstalk. In addition to these variations, the work in [10] explored the impact of optical loss non-uniformity among MZIs and showed SP-NN performance degradation.…”
Section: Related Prior Workmentioning
confidence: 99%
See 3 more Smart Citations
“…While several high-performance AI accelerators based on coherent SP-NNs have been recently proposed [2,10,13], [14] showed that the inferencing accuracy of SP-NNs can drop by up to 70% due to fabrication-process variations and thermal crosstalk. In addition to these variations, the work in [10] explored the impact of optical loss non-uniformity among MZIs and showed SP-NN performance degradation.…”
Section: Related Prior Workmentioning
confidence: 99%
“…In (4), 𝑁 𝑀𝑍 𝐼 is the total number of MZIs in the OIU in layer 𝐿 𝑚 and 𝑃 is the input optical power. Moreover, 𝑋 𝑚 𝑗 𝑀𝑍 𝐼 (𝜌) can be calculated using (2) and is the coherent crosstalk on the output of layer 𝐿 𝑚 originating in MZI 𝑗 in the OIU. Also, 𝜌 is the optical phase of the crosstalk signal.…”
Section: Layer-level Compact Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…More advanced structures have been shown in the literature where both photonic accelerators (devices specialized to perform a single function and which are interfaced with electronic computer) [178,179] or photonic integrated neural networks [180][181][182][183] with extremely high capacity and speed [184,185] are demonstrated.…”
Section: Neuromorphic Photonicsmentioning
confidence: 99%